Evaluation of the Correlation Between Strength and Special Training Indicators in Mixed Martial Arts - Andrii Chernozub; Oleh Olkhovyi; Alla Aloshyna; Andrii Savenko; Ivan Shtefiuk; Ivan Marionda; Tetiana Khoma; Victoriya Tulaydan (Physical Education Theory and Methodology, 2023)
Study purpose. To study the peculiarities of correlation between the maximum strength development and quantity of kicks in MMA using load regimes of different intensity and energy supply.